Pathogenesis of Staphylococcus haemolyticus on primary human skin fibroblast cells - Hala O. Eltwisy (Taylor & Francis Group, 2020)
Staphylococcus haemolyticus (S. haemolyticus) is one of the Coagulase-negative staphylococci (CoNS) that inhabits the skin as a commensal. It is increasingly implicated in opportunistic infections, including diabetic foot ulcer (DFU) infections. In contrast to the abundance of information available for S. aureus and S. epidermidis, little is known about the pathogenicity of S. haemolyticus, despite the increased prevalence of this pathogen in hospitalized patients. We described, for the first time, the pathogenesis of different clinical isolates of S. haemolyticus isolated from DFU on primary human skin fibroblast (PHSF) cells. Virulence-related genes were investigated, adhesion and invasion assays were carried out using Giemsa stain, transmission electron microscopy (TEM), MTT and flowcytometry assays. Our results showed that most S. haemolyticus carried different sets of virulence-related genes. S. haemolyticus adhered to the PHSF cells to variable degrees. TEM showed that the bacteria were engulfed in a zipper-like mechanism into a vacuole inside the cell. Bacterial internalization was confirmed using flowcytometry and achieved high intracellular levels. PHSF cells infected with S.haemolyticus suffered from amarked decrease in viability and increased apoptosis when treated with whole bacterial suspensions or cell-free supernatants but not with heat-treated cells. After co-culture with PBMCs, S. haemolyticus induced high levels of pro-inflammatory cytokines. This study highlights the significant development of S. haemolyticus, which was previously considered a contaminant when detected in cultures of clinical samples. Their high ability to adhere, invade and kill the PHSF cells illustrate the severe damage associated with DFU infections. Abbreviations CoNS, coagulase-negative staphylococci; DFU, diabetic foot ulcer; DM, diabetes mellitus; DMEM, Dulbecco’s Modified Eagle Medium; MTT, 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide; PBMCs,peripheral blood mononuclear cells; PHSF, primary human skin fibroblast; CFU, colony-forming unit.